2015
DOI: 10.1002/ajoc.201500232
|View full text |Cite
|
Sign up to set email alerts
|

Mizoroki–Heck Reaction of Aryl Halides and Dialkyl Allylphosphonates in Water Catalyzed by Reusable Palladium Nanoparticles

Abstract: Commercial [PdCl 2 (NH 3 ) 2 ]w as appliedt oc atalyze the Mizoroki-Heck coupling of aryl halides with dialkyl allylphosphonates using iPr 2 NH as the base in water under aerobic conditions. The reactionw as conducted at8 08C( for aryl iodides) or 120 8C( for aryl bromides) for 36 h, giving the correspondinga ryl-substituted allylphosphonates in good to excellent yields, and both water-soluble and insoluble aryl halidesc ould be utilized in this reaction. After extracting the reaction solution with ethyl aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In previous studies, we found that i Pr 2 NH is the best base to employ for the coupling of aryl halides and dialkyl allylphosphonates; 92 therefore, it was also used as the base in the Mizoroki-Heck reaction of aryl halides and dialkyl vinylphosphonate. As shown in Table 1, iodobenzene 1a (1 mmol), diethyl vinylphosphonate 2a (2 mmol), i Pr 2 NH (1.1 mmol), and PdCl 2 (NH 3 ) 2 (5 mol%) were reacted in an open-air reactor at 80 C using water (3 mL) as the solvent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we found that i Pr 2 NH is the best base to employ for the coupling of aryl halides and dialkyl allylphosphonates; 92 therefore, it was also used as the base in the Mizoroki-Heck reaction of aryl halides and dialkyl vinylphosphonate. As shown in Table 1, iodobenzene 1a (1 mmol), diethyl vinylphosphonate 2a (2 mmol), i Pr 2 NH (1.1 mmol), and PdCl 2 (NH 3 ) 2 (5 mol%) were reacted in an open-air reactor at 80 C using water (3 mL) as the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Use of this catalyst without an auxiliary ligand to fulll the Mizoroki-Heck reaction has been described previously, in which Pd nanoparticles were formed during the coupling reaction. 92 The reaction rates of vinylphosphonates were faster than those of allylphosphonates, which may be due to the electron-withdrawing phosphonate group of 2a becoming attached directly to the vinyl carbon, which lowers the p* energy level of the olen, facilitating coordination of the p bond to palladium. Then, the catalyst loading was further reduced to 0.1 mol%, resulting in 68% and 70% product yields, respectively, with a prolonged reaction time (Entries 7 and 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation